2022
DOI: 10.1080/20002297.2022.2052632
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the oral microbiome of burning mouth syndrome patients

Abstract: Burning mouth syndrome (BMS) is a chronic pain condition accompanied by unpleasant burning sensations of the oral mucosa. While multiple factors were proposed for the etiology, evidence suggested a neuropathic pain origin while others suspected the use of antibiotics as the underlying cause. Interestingly, several reports demonstrated the intimate interaction of the nervous system and the microbiome. The current study aims to elucidate the correlation of the oral microbiome with the pathophysiology of the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…For instance, LPS derived from the odontogenic pathobiont Porphyromonas gingivalis can elicit dose-dependent calcium influx and inward currents, sensitizes TRPV1 to capsaicin, and stimulates the release of calcitonin gene-related peptide in trigeminal ganglia (Diogenes et al, 2011) correlated to the abundance of some bacterial taxa, suggesting a potential causal relationship (Fourie et al, 2016). Another study carried out with burning mouth syndrome patients found similar results, concluding that a higher abundance of Streptococcus, Granulicatella, Bergeyella, and Rothia genus in the oral microbiome was associated with this chronic pain condition (Lee et al, 2022). Nonetheless, further research is necessary to decipher the underlying mechanisms involved in the role of these oral bacteria in chronic pain.…”
Section: Iv3 Other Anatomical Regions Of Dysbiosis Potentially Involv...mentioning
confidence: 78%
“…For instance, LPS derived from the odontogenic pathobiont Porphyromonas gingivalis can elicit dose-dependent calcium influx and inward currents, sensitizes TRPV1 to capsaicin, and stimulates the release of calcitonin gene-related peptide in trigeminal ganglia (Diogenes et al, 2011) correlated to the abundance of some bacterial taxa, suggesting a potential causal relationship (Fourie et al, 2016). Another study carried out with burning mouth syndrome patients found similar results, concluding that a higher abundance of Streptococcus, Granulicatella, Bergeyella, and Rothia genus in the oral microbiome was associated with this chronic pain condition (Lee et al, 2022). Nonetheless, further research is necessary to decipher the underlying mechanisms involved in the role of these oral bacteria in chronic pain.…”
Section: Iv3 Other Anatomical Regions Of Dysbiosis Potentially Involv...mentioning
confidence: 78%
“…Due to the longer amplicon size of the V1-V3 region compared to V3-V4, the merge rate of the paired-end reads is higher in the V3-V4region than in the V1-V3region [18]. And many recent studies reported that V3-V4 regions could be used for oral microbiota studies [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Qiime2 was used for the diversity analysis and taxonomic classification, while the Naïve Bayes classifier (Greengenes13_8 99% OTU full-length sequence) was employed for only taxonomic classification. The phylum, genus, and species were extracted from taxa with relative abundance > 1% of the total in the Down syndrome or non-Down syndrome groups, according to the method previously described 28 . All findings related to bacterial phyla, genera, and species obtained from microbiome analysis were validated and polished using the eHOMD (Human Oral Microbiome D) and LPSN databases.…”
Section: Methodsmentioning
confidence: 99%